2014
DOI: 10.21608/ejaj.2014.63617
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Compost and Compost tea as Promising Method for Meloidogyne Incognita Management

Abstract: Two types of compost, (plant and animal) as well as furan 10%G were effective in reducing Meloidogyne incognita number of galls, nematode reproduction and fecundity. Compost was investigated as amendment for suppressing populations of Meloidogyne incognita and increasing plant vigor. The greenhouse and laboratory studies were conducted with mature compost produced in SEKEM organic farm. Compost extract was prepared by steeping 100 g compost in 200 ml tap water and removing biomass with cheesecloth filtration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Similarly, it was reported that cattle manure, sheep manure and chicken manure as soil amendments at different rates of 2, 4 and 6 ton/ feddan reduced females, galls and egg-mass numbers of M. arenaria infesting sugar beet as compared to un-amended plants (Ismail & Mohamed, 2012). Moreover, Abdel-Bary et al, (2014) found that animal compost reduced final population of Meloidogyne sp., ranged from 73.57 to 92.18% and the plant compost caused reduction ranged from 71.92 to 92.54%. The usage of soil amendments is a conventional agricultural practice to control pathogens in soil, improve physical and chemical soil properties, soil structure, temperature and humidity conditions as well as nutrients content which are needful for plants growth.…”
Section: Data Presented Inmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, it was reported that cattle manure, sheep manure and chicken manure as soil amendments at different rates of 2, 4 and 6 ton/ feddan reduced females, galls and egg-mass numbers of M. arenaria infesting sugar beet as compared to un-amended plants (Ismail & Mohamed, 2012). Moreover, Abdel-Bary et al, (2014) found that animal compost reduced final population of Meloidogyne sp., ranged from 73.57 to 92.18% and the plant compost caused reduction ranged from 71.92 to 92.54%. The usage of soil amendments is a conventional agricultural practice to control pathogens in soil, improve physical and chemical soil properties, soil structure, temperature and humidity conditions as well as nutrients content which are needful for plants growth.…”
Section: Data Presented Inmentioning
confidence: 99%
“…The usage of mineral salts, organic acids, amino acids, growth regulators, mineral fertilizer, and organic matters are probably one of the possible novel alternatives and environmentally safe management practices against plant parasitic nematode infestations, as well as promoting plant growth and increasing its resistance (Pankaj & Sharma, 2003;Al-Ghonaimy & Zawam, 2016;Radwan et al, 2017). In addition the utilization of organic amendments such as cattle, chicken, sheep and horse manures and others were very effective tools against plant parasitic nematodes at different crops (Ismail & Mohamed, 2012;Renco, 2013;Abdel-Bary et al, 2014). This investigation aimed to study the nematicidal impacts of some mineral salts, organic acids, amino acids, growth regulators, mineral fertilizer and organic matters against root-knot nematode, Meloidogyne incognita in vitro and in vivo conditions.…”
mentioning
confidence: 99%